Poklicna identiteta in etika v socialnem delu v objavah v reviji Socialno delo - Sobočan, Ana Marija (Socialno delo, 2019)
To uncover how do papers, published in the scientific journal Socialno delo Social work (or its predecessors) cover the topic of ethics, as well as social work professional identity, a number of texts, published between 1972 and 2018 is discussed. By doing this, it sheds light on the themes and orientations, which have - by publication in the journal - contributed to the theoretical, interpretative grounds and views on ethics and social work identity in Slovenia. This grounds are definitely relevant for the understandings and legitimations of what is social work in Slovenia, what are its goals, values, authority, limitations, etc., so it would be reasonable to ponder and publish even more on ethics and professional identity than until now.
Keywords: etična načela; etični kodeks; izobraževanje; socialno delo; vrednote